SAT0477 The impact of advanced clinician practitioner in arthritis care (ACPAC) program-trained extended role practitioners on healthcare delivery in ontario: A two year prospective study. (23rd January 2014) - Passalent, L.; Kennedy, C.; Soever, L.; Warmington, K.; Brooks, S.; Shupak, R.; Lundon, K.; Schneider, R.
Abstract : Background: The Advanced Clinician Practitioner in Arthritis Care (ACPAC) training program focuses on the assessment, diagnosis, triage and independent management of selected musculoskeletal and arthritis-related disorders.It is offered to experienced physical and occupational therapists. Objectives: The objectives of this study were: 1) to examine the clinical performance of ACPAC program-trained Extended Role Practitioners (ERPs) and 2) to evaluate the extent to which these ERPs are delivering integrated and timely healthcare. Methods: ACPAC ERPs (n=30) from 15 healthcare institutions across Ontario (urban, rural, academic, non-academic, adult and paediatric) completed a longitudinal survey each quarter for 2009 and 2010. Indicators were developed via consensus and pilot testing. Analyses were descriptive. Results: Response rate varied from 83-97% across quarters. ERPs saw 13407 and 14546 patients in 2009 and 2010, respectively. In 2009, the majority of patients were referred by a family physician (43.9%), and 35.8% by a specialist. This shifted in 2010 to 37.3% and 51.5%, respectively. Over the two-year period, combined adult and paediatric caseloads included new consults (24.9%) and follow-ups (55.6%). Remaining patients underwent triage by an ERP. Most common patient diagnoses included: osteoarthritis (51.6%), rheumatoid arthritis (14.7%) and juvenile idiopathic arthritis (11.1%). About 90% of respondents were working in an extended practice role. The longest median wait time from referral to initial assessment by an ERP was 22 days. Approximately half of ERPs participate in each of: education delivery, research and leadership roles, with the majority pursuing professional development. Approximately one third of patients were referred, by an ERP, for x-rays, lab tests and other services (i.e. splints, footwear), followed by referral to allied health services and specialists, and communication via dictated letters. As many as 79% of ERPs acted under the auspices of medical directives, ordering x-rays (over 80%), lab tests (over 60%) and diagnostic ultrasounds (over 40%). Approximately 70% recommended medication/dosage changes (up to 14% made these changes independently). Approximately 90% recommended joint injections (up to 18% performed them). Conclusions: ACPAC program-trained therapists are primarily seeing patients with osteoarthritis or rheumatoid arthritis in a follow-up capacity, with most patients referred by a family physician or specialist. Most ERPs are utilizing medical directives to support their extended practice roles. This new human health resource may be an effective way to address the progressive decline in arthritis care specialists. Future evaluations should monitor the evolution of ERPs' extended roles and assess the impact of ERP-based care on patient outcomes. Disclosure of Interest: None Declared